What Common Ground Exists for Descriptive, Prescriptive, and Normative Utility Theories? - Luce, R. Duncan; von Winterfeldt, Detlof (Management Science, 1994)
Descriptive and normative modeling of decision making under risk and uncertainty have grown apart over the past decade. Psychological models attempt to accommodate the numerous violations of rationality axioms, including independence and transitivity. Meanwhile, normatively oriented decision analysts continue to insist on the applied usefulness of the subjective expected utility (SEU) model. As this gap has widened, two facts have remained largely unobserved. First, most people in real situations attempt to behave in accord with the most basic rationality principles, even though they are likely to fail in more complex situations. Second, the SEU model is likely to provide consistent and rational answers to decision problems within a given problem structure, but may not be invariant across structures. Thus, people may be more rational than the psychological literature gives them credit for, and applications of the SEU model may be susceptible to some violations of invariance principles. This paper attempts to search out the common ground between the normative, descriptive, and prescriptive modeling by exploring three types of axioms concerning structural rationality, preference rationality, and quasi-rationality. Normatively the first two are mandatory and the last, suspect. Descriptively, all have been questioned, but often the inferences involved have confounded preference and structural rationality. We propose a prescriptive view that entails full compliance with preference rationality, modifications of structural rationality, and acceptance of quasi-rationality to the extent of granting a primary role to the status quo and the decomposition of decision problems into gains and losses.